1992
DOI: 10.1111/j.1365-3059.1992.tb02334.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of stomatal frequency and morphology in Lycopersicon species with resistance to Xanthomonas campestris pv. vesicatoria

Abstract: Study of the stomata and leaf epidermis of eight Lycopersicon species has revealed a relationship between frequency of stomata, stomatal size and some morphological leaf characteristics, and resistance to bacterial leaf spot caused by Xanthomonas campestris pv. vesicatoria. Significant correlations were found between the stomatal frequency in both adaxia! and abaxial leaf epidermis and the number of bacterial lesions per leaf area (/-= 0-70 and 0-68, respectively) and the frequency of stomata in both adaxial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
(21 reference statements)
0
10
0
2
Order By: Relevance
“…Thus, slightly lower numbers of stomata between veins on the abaxial surface of the resistant genotype which are additionally occluded by wax in both genotypes might contribute to lower numbers of bacteria entering the intercellular space in the resistant plant. In bacterial leaf spot of tomato, stomatal frequency and morphology were shown to be associated with resistance to the disease (Ramos et al, 1992). For a conclusive interpretation of the role of leaf stomata in cassava bacterial blight infection it should be considered, that stomata distribution might change under differing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, slightly lower numbers of stomata between veins on the abaxial surface of the resistant genotype which are additionally occluded by wax in both genotypes might contribute to lower numbers of bacteria entering the intercellular space in the resistant plant. In bacterial leaf spot of tomato, stomatal frequency and morphology were shown to be associated with resistance to the disease (Ramos et al, 1992). For a conclusive interpretation of the role of leaf stomata in cassava bacterial blight infection it should be considered, that stomata distribution might change under differing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a peach cultivar with high susceptibility towards X. c. pv. Ramos et al (1992) found a correlation of the stomatal width as well as the stomatal frequency with the number of lesions caused by X. c. pv. Similar Initial events in pathogenesis 201 differences in stomatal aperture have been reported in X. c. pv.…”
Section: Conditions Which Favour Penetrationmentioning
confidence: 91%
“…vesicatoria was obtained by Ramos et al (1992). Evidence for a structurally conditioned resistance of Lycopersicon species to X. c. pv.…”
Section: Anatomic Featuresmentioning
confidence: 99%
“…Resultados similares foram observados nos patossistemas Lycopersicon spp.-Xanthomonas campestris pv. vesicatoria (14), amendoim-Phaeoisariopsis personata (18) e triticale-Tilletia indica (7).…”
Section: Ide-notas Idn-notasunclassified